Androgynous Perspective as Represented on The Offspring’s Why Don’t You Get A Job? - Cahyaningsih Pujimahanani; Salsabila Nova Calista; Laila Nabilahtauzzahro Ibrahim; Rommel Utungga Pasopati (Universitas Pendidikan Indonesia, 2023)
Literatures are meanings of everyday life as on point with Sandra Bem’s concept about androgynous sides that focuses on indicating masculinity and femininity of individuals and societies. Why Don’t You Get a Job? is a song by The Offspring in 1999 that underlines American couples’ condition where only one side is working while the other is doing nothing. Interestingly, this band shows how that situation happens to both gender. Then, how is androgynous perspective represented on The Offspring’s Why Don’t You Get a Job?? Through qualitative method, this paper exposes that man and woman are proved not to be so independent and dependent, but both should work to complement each other. That song indicates that society is so androgynous that spots roles of man and woman supported by Bem’s theory. In conclusion, the song shows society is not totally about man or woman but how each side asks other side for better deed. The Offspring asserts androgynous perspective that requires roles of man and woman, not of being dominant but to be complementary.